2020
DOI: 10.2463/mrms.mp.2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging-based Evaluation of Mesenteric Ischemia Caused by Strangulated Small Bowel Obstruction and Mesenteric Venous Occlusion: An Experimental Study Using Rabbits

Abstract: Purpose: This study assessed the MRI findings of strangulated small bowel obstruction (SBO) and mesenteric venous occlusion (MVO) in a rabbit model using 3T MRI. Materials and Methods:Twenty rabbits were included in this study. The strangulated SBO and MVO models were generated via surgical procedures in nine rabbits, and sham surgery was performed in two rabbits. The success of generating the models was confirmed via angiographic, macroscopic, and microscopic findings after the surgical procedure. MRI was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Previous preclinical studies found an increase in necrotic bowel wall signal intensity on T2-WI. [21][22][23] However, higher MRI field-strength (3.0 or 7.0 T) and smaller animals (rats, rabbits, cats) were used, thus making it difficult to extrapolate the results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous preclinical studies found an increase in necrotic bowel wall signal intensity on T2-WI. [21][22][23] However, higher MRI field-strength (3.0 or 7.0 T) and smaller animals (rats, rabbits, cats) were used, thus making it difficult to extrapolate the results.…”
Section: Discussionmentioning
confidence: 99%
“…To remain consistent with the study by Bruhn et al, 24 we used the contrast between the ischemic and nonischemic bowels normalized to the spinal muscle. Such normalization has been used previously 23 and was necessary since pigs were moved to and from the operating room to assess bowel viability during the experiment, thus modifying the background noise and limiting signal reproducibility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations